Kepemimpinan Kepala Madrasah Dalam Meningkatkan Profesionalisme Guru Di MAS Miftahussalam Medan - Wiwik Indah Lestari; Nurhalima Tambunan (Yayasan Rahmat Islamiyah, 2025)
This research aims to describe the role of the madrasah principal in strengthening teacher professionalism, along with the supporting and hindering factors, within the context of MAS Miftahussalam Medan. The study uses a qualitative descriptive method with a case study approach. The research subjects include the principal and teachers. Data were collected through observation, interviews, and document analysis. The data were analyzed using techniques of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation. The findings show that: (1) the principal’s managerial skills significantly contribute to improving teacher professionalism at MAS Miftahussalam Medan, although they are not yet fully optimal and require strong collaboration from all school components; and (2) the principal plays a key role in creating a harmonious environment by assigning tasks according to each teacher’s role and supporting their professional development.